Combustion of micro wax from polyethylene pyrolysis. Issue 7 (3rd July 2018) - Lasek, J.; Hrycko, P.; Wasielewski, R.; Kopczyński, M.; Bodora, K.; Kaczmarzyk, G.; Adamczyk, M.
ABSTRACT: Combustion of micro wax from polyethylene pyrolysis has been studied using technical-scale combustion chamber (height of 3.4 m and diameter of 0.6 m). Physical and chemical properties of micro wax (a mixture of wax and oil) were determined as basis investigations. Some fractions of hydrocarbons after condensation of pyrolysis products still are needed to be utilized. The aim of these investigations was to confirm a possibility of micro wax application as a liquid fuel. The combustion process was stable and emission properties (NOx, SOx, CO, VOCs, TOCs, PAHs) were determined. These investigations show that micro wax from polyethylene pyrolysis can be used as a liquid fuel for stationary combustion chambers.